2014
DOI: 10.22518/2462909x.263
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment and Leadership in Higher Education Institutions

Abstract: The proposed research aims to determine the relationship between dean´sleadership and organizational commitment among faculty at universities in Colombia. A quantitative research design will guide the study to determine therelationship among leadership style of deans and organizational commitment. The multifactor leadership questionnaire (MLQ) developed by Bass in 1985 andthe organizational commitment questionnaire (OCQ) developed by Meyer andAllen in 1999 will be the instruments administered to collect the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The statements used for measuring OC were adapted from questionnaires developed by (Allen and Meyer, 1990; Porter and Smith, 1970), with necessary modifications to suit the present research context. Using a five-point Likert scale respondents were asked to rate their level of agreement on each statement from “1” as “strongly disagree” to “5” as “strongly agree.” Several author researchers (BinBakr and Ahmes, 2015; Bohórquez, 2014; Juhdi and Hamid, 2009; Mowday et al , 1979) have used these scales in university context for determining OC-JS in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…The statements used for measuring OC were adapted from questionnaires developed by (Allen and Meyer, 1990; Porter and Smith, 1970), with necessary modifications to suit the present research context. Using a five-point Likert scale respondents were asked to rate their level of agreement on each statement from “1” as “strongly disagree” to “5” as “strongly agree.” Several author researchers (BinBakr and Ahmes, 2015; Bohórquez, 2014; Juhdi and Hamid, 2009; Mowday et al , 1979) have used these scales in university context for determining OC-JS in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…Sample items include: (a) normative commitment—‘I feel a moral obligation to remain with my current employer’, (b) affective commitment—‘Right now, staying with this university is a matter of necessity’ and (c) continuance commitment—‘I feel that I have very few options to consider leaving my university’. Several author researchers (Alam, 2011; Bohorquez, 2014; Nawab & Bhatti, 2011) have used Allen and Meyer’s questionnaire for determining organisational commitment in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies reveal that various factors can lead to increased organizational commitment (Astuty, 2022;Khuong, 2022;Pham-Thi-Hong, 2023;Santana-Martins, 2022). One of the many antecedents that encourage increased organizational commitment is spiritual leadership (Bohórquez, 2014;Febrianto et al, 2019;Jeon & Choi, 2020;Wong et al, 2015). The results of research conducted by Febrianto et al (2019); Jeon & Choi (2020); Yang & Fry (2018) found that spiritual leadership has a significant effect on organizational commitment, while the results of research by Bohórquez (2014); Wong et al (2015) show that spiritual leadership has no significant effect on organizational commitment.…”
Section: Introductionmentioning
confidence: 99%